Brand Image and Reputation's Psychological Effects on Long-term Company Performance in Indonesian Logistics - Negara, Danes Jaya; Mantikei, Ferdinand, Bambang; Meitiana; Christa, Usup Riassy; Sintani, Lelo; Mering, Laden (Current Topics on Business, Economics and Finance Vol. 4, 2023)
Theoretically, there is a connection between a brand's reputation, goodwill, and long-term business success (FP). The goal was to investigate the psychological impact of brand reputation and brand image on the long-term financial performance of Indonesian logistics enterprises. That was accomplished utilizing first-hand information gathered through questionnaires. The distribution of 500 questionnaires resulted in 270 valid replies being used for data analysis by logistics companies using Smart PLS. The study's findings showed that brand reputation and image had a significant psychological impact on the long-term financial performance of logistics organizations. Each modification of the brand's reputation and image has a profound psychological impact that can either increase or decrease the sustained FP. The essential conclusion supported by these results is that The psychological impact of any change to the brand's reputation and image has a considerable impact on whether the sustainable FP is higher or lower. As a result, logistics companies should improve their brand reputation and image. Moreover, goodwill plays a crucial part in sustainable FP. Brand reputation and image have an impact on brand goodwill, which in turn has an impact on sustainable financial performance.